Material Analysis in Cultural Heritage - Šmit, Žiga; Menart, Eva (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
"Material Analysis in Cultural Heritage" describes the application of modern analytical techniques in the studies of selected historical materials, their properties, and processes they undergo. The topics include glass and ceramics, metal preservation, functionality and testing of historic and modern building materials, origins of specific stones, decomposition of painting pigments, and the construction of historic violins.